The Effectiveness of the Montessori Method in Shaping Children's Character: A Case Study on the Formation of Moral and Religious Values in Children Aged 3–6 Years at Alifa Muslim Montessori Yogyakarta - Nabila Khairun Nisa’; Sudarmadi; Anip Dwi Saputro (ISTAWA, 2023)
This study aims to examine the effectiveness of the Montessori method in shaping children's character, focusing on the development of moral and Islamic values in children aged 3–6 years at Alifa Muslim Montessori Yogyakarta. A mixed-method approach with an exploratory sequential design was employed. The qualitative approach involved descriptive case studies through observation, interviews, and documentation, while the quantitative approach used questionnaires with Respondent Achievement Rate (TCR) and regression analysis. Findings indicate that the Montessori method plays a significant role in fostering focus, independence, and moral awareness among children. It also enhances their ability to internalize religious values through daily practices such as prayer, honesty, responsibility, and empathy. Quantitative results show that the effectiveness of the Montessori method is categorized as 'Good' for variable X (82%) and 'Very Good' for variable Y (88%). Regression analysis reveals that 47.7% of character formation is influenced by the Montessori method, while 52.3% is explained by other factors. Thus, the Montessori method is proven effective in supporting the holistic development of children's moral and religious character in early childhood education.